ANALISIS TINDAK TUTUR FRASA ’PENUH DENGAN ROH KUDUS’ DALAM KISAH PARA RASUL 6–7: STUDI PRAGMATIK TERHADAP KONSTRUKSI OTORITAS SPIRITUAL STEFANUS - Fiona Isaura Talifuddin; Yolanda Nany Palar (Institut Agama Kristen Negeri Manado, 2025)
The book of Acts emphasises the active role of the Holy Spirit in the development of the early church. One of the phrases that is explicitly repeated in the narrative is the phrase